ØªØ£Ø«ÙŠØ± Ø§Ø³Ù„ÙˆØ¨ Think Pair Share Ø¹Ù„Ù‰ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ØµÙ Ø§Ù„ØØ§Ø¯ÙŠ Ø¹Ø´Ø± ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ù‡Ø¯Ø§ÙŠØ© Ø§Ù„Ù„Ù‡ Ù…ØªØ§Ø±Ø§Ù… - Suci Wulandari; Suparmanto Suparmanto; M. Syarifuddin (Lughatu Ad-Dhat, 2023)
The reason the researcher took the title of this study was to find out the effect of Think Pair Share on Maharah reading in language subjects. So the purpose of this study is to find out how influential the think pair share model is on reading skills in learning Arabic. The population in this study were all students of class XI at the Hidayatullah Mataram School and the researchers took 25 students from this population to be sampled in this study. The research approach used is quantitative research. In collecting data, researchers used three research instruments, namely questionnaires, documentation, and observation.Â The data analysis uses product moment correlation and simple regression with the help of SPSS 16.0 software. based on the results of the correlation analysis, a positive and significant relationship was obtained with a correlation level of R = 66.2% indicating a strong relationship between the two variables. And as for the results of the regression analysis the researcher obtained an R count > R table rcount 0.662 > 0.396 with a significance rate of 0.00 <0.05 so it can be concluded that there is an influence of Think Pair Share (X) on Maharah Qiroah (Y) with the contribution of Think Pair Share (X) to Maharah Qiroah (Y) of Rsquare = 43.9% , therefore, the hypothesis that says